PENGARUH GAYA KEPEMIMPINAN, DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. SKYLINE JAYA - Ade Reza Ihsani; Indro Kirono (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to examine the influence of leadership style, work discipline and motivation on employee performance at PT. Skyline Jaya. The information obtained from the results of this study can be used as input for further researchers and the company PT Skyline Jaya. The population used in this study were all employees working at PT Skyline Jaya, totaling 100 people with a saturated sample technique, namely a sampling technique in which all members of the population are sampled. The data source in this study is primary data, namely the results of distributing questionnaires to the respondents, namely employees of PT Skyline Jaya. The type of data used is subjective data in the form of written responses in response to a questionnaire. The analytical model used in this study is a multiple linear regression analysis model. To find out the significance of the research variables partially on employee performance, the t test technique is used. By using a level of 5% or 0.05. The results show that leadership style, work discipline and motivation have an effect on employee performance. Suggestions for companies, it is hoped that this research needs to increase employee behavior in terms of good work discipline so that work is completed on time and can improve employee performance and for further researchers the results of this study can be used as a reference by increasing the number of variables and using different analysis techniques and provides a broader picture of what factors affect employee performance besides leadership style, discipline and motivation.